THE EFFECTIVENESS OF DISCOVERY LEARNING MODEL IN IMPROVING STUDENTS’ FICTION WRITING (Indonesian Journal of Learning and Instruction, 2018)
Writing skill becomes a concern nowadays since it is an important skill in communication and becomes the hallmark of a creative, imaginative, and educated nation. Yet, in fact, students’ writing skills are generally low which can be seen from the lack of quality of writing produced. This is caused by some factors, including the lack of time allocation provided by the teacher to practice writing, the lack of teachers’ creativity in using learning models that can stimulate students to write, and the low of students’ reading habits. Hence, this study aims to identify the effectiveness of Discovery Learning (DL) model in improving students’ fiction writing. This research is a quasi experimental with nonequivalent control group design. The sample of research was the fourth grader of elementary school in Purwakarta sub-district. The data in this research were collected through writing test, observation, and interview. Moreover, students’ writing skills were assessed by using writing rubric which has been validated by expert lecturers. Further, the data were then analyzed by using inference statistics including normality test, homogeneity test, and t-test. The results revealed that discovery learning model is effective in improving students’ fiction writing which can be seen from students’ post test score. This is because discover learning model allows students to explore, classify, and utilize more data to improve their imagination, their vocabulary selection, and their creativity as well.Keywords: discovery learning model; writing skill; fiction writing.